2018
DOI: 10.1016/j.ausmj.2018.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Purchase Intention of Electric Vehicles in Hong Kong

Abstract: What makes consumers adopt energy-sustainable innovations? Drawing from psychological research on environmental behaviors, we propose a model integrating attitudinal factors, normative factors and self-control to explain the purchase of electric vehicles (EVs) by consumers. Specifically, we utilized structural equation modeling to develop a model to identify relationships between perceived values, green attitudes, normative factors, and self-expressive benefits and purchase intention of EVs. An empirical study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 77 publications
(83 reference statements)
3
34
0
2
Order By: Relevance
“…In this respect, price is defined as the monetary value attached to the product by its seller and the resulting money disbursed on that product by the customer. Although the price of EVs is generally higher than that of most comparable alternatives [59], some research studies have shown that concern for the environment influences some consumers' willingness to pay these higher prices [71], though other studies have contradicted these findings [72]. In addition to this, several studies have found that price is a barrier to many potential adopters [25,73,74].…”
Section: The Role Of Financial and Technical Attributes In The Adoptimentioning
confidence: 99%
“…In this respect, price is defined as the monetary value attached to the product by its seller and the resulting money disbursed on that product by the customer. Although the price of EVs is generally higher than that of most comparable alternatives [59], some research studies have shown that concern for the environment influences some consumers' willingness to pay these higher prices [71], though other studies have contradicted these findings [72]. In addition to this, several studies have found that price is a barrier to many potential adopters [25,73,74].…”
Section: The Role Of Financial and Technical Attributes In The Adoptimentioning
confidence: 99%
“…While China's physical size and vast population represent great opportunities for marketers, there are also numerous hurdles to overcome at every stage of the marketing process – from distribution and quality assurance to promotional activities (Sinclair, 2018). The market is constantly changing and growing; becoming increasingly more sophisticated and monetarily more valuable by the day (Woetzel et al, 2019; Nielsen, 2019; Liu et al, 2016a). Such a dynamic marketplace makes it difficult to gain a real understanding of Chinese audiences whose preferences and tastes change so rapidly that companies find it increasingly hard to keep up (Brink Asia, 2016; Li et al, 2008).…”
Section: Background and Research Hypothesesmentioning
confidence: 99%
“…Nilai yang dirasakan adalah pendapat konsumen tentang nilai produk atau layanan berdasarkan evaluasi utilitasnya (Chen dan Chang, 2012). Nilai yang dirasakan memainkan peran yang penting dalam menentukan proses pengambilan keputusan konsumen Dodds, et al dan Monroe (2014) dan menentukan niat pembelian dan perilaku merek (Chen dan Chang, 2012; Chiu, Lee, dan Chen, 2014;Ng et al, 2018;Yadav dan Pathak, 2017). Konsumen akan mengevaluasi biaya dan manfaat secara subjektif ketika mereka membeli suatu produk.…”
Section: Perceived Value (Pv)unclassified